Enhanced particle swarm optimization based on weighted least square method - A. Hussein, Mothafer; Ahmed Jasim Sultan, Asst. Prof (International Journal of Engineering and Technology, 2019)
with the increase of population, electrical power systems have grown with more complexity. This complexity leads to increase the focusing on the monitoring and control system of power systems. State estimation on of the recent techniques that are used to enhance the monitoring of the power system, however traditional state estimation is one of the methods that are not enough by themselves, though optimization methods are needed to enhance the results of state estimation. PSO algorithm is an artificial intelligence optimization method which can be used to enhance the WLS estimation method. Traditional PSO-WLS has showed its efficiency however in this paper an enhancement is done to PSO method to utilize the same number of iterations to achieve better estimation. The proposed method is proved by using MATLAB simulation and applied on standard IEEE-14 bus.Â Â
Keywords: PSSE; WLS; PSO; State Estimation; Power System; Optimization; Artificial Intelligence.